The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1080/21507716.2012.714837
|View full text |Cite
|
Sign up to set email alerts
|

Proximity, Ethical Dilemmas, and Community Research Workers

Abstract: Background:In community-engaged research (CEnR), recruitment and data collection are often assigned to community research workers (CRWs). CRWs are hired because of close ties with target communities and presumed greater success recruiting and gathering data from marginalized populations. The value conflicts and personal stress facing CRWs have been described in the international context; however, less attention has been paid to these issues in U.S. settings. Methods: Qualitative interviews were held with CRWs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 28 publications
1
30
0
1
Order By: Relevance
“…Respondents met frequently with their principal investigator and perceived their organizations as dedicated to research ethics and providing clear performance expectations. However, consistent with our focus-group findings and previous qualitative studies (Alexander and Richman 2008; Richman, et al 2012; True et al 2011), approximately 40% endorsed items indicating their organization did not provide counseling for job-related stress and had unrealistic demands for recruitment numbers and multiple staff role assignments. As predicted, a positive organizational climate was associated with a strong research commitment and with lower levels of moral stress, research mistrust, and moral practice dilemmas.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Respondents met frequently with their principal investigator and perceived their organizations as dedicated to research ethics and providing clear performance expectations. However, consistent with our focus-group findings and previous qualitative studies (Alexander and Richman 2008; Richman, et al 2012; True et al 2011), approximately 40% endorsed items indicating their organization did not provide counseling for job-related stress and had unrealistic demands for recruitment numbers and multiple staff role assignments. As predicted, a positive organizational climate was associated with a strong research commitment and with lower levels of moral stress, research mistrust, and moral practice dilemmas.…”
Section: Discussionsupporting
confidence: 88%
“…Our national survey thus provides some insights into the characteristics of individuals responsible for the implementation of this important work. First, while small sample qualitative studies have focused on staff drawn from the community for their insider knowledge (Alexander and Richman 2008; Andrews et al 2004; Berg et al 2004; Hill et al 1996; Nilsson et al 2011; Richman et al 2012; Sunderland et al 2011; Terpstra et al 2011; True et al 2011), in our survey a majority of respondents were college educated and many held graduate degrees. Regardless of educational status, 70% had lived in communities in which they conduct research and a quarter reported a personal history of drug use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given their lay position, community recruiters are highly effective at recruitment of especially hard to reach populations. However, this recruitment and access method does not come without challenges to the scientific process [45]. In this study, these challenges manifested around issues of recruitment and eligibility.…”
Section: Discussionmentioning
confidence: 97%
“…Third, researchers involved in collaborative research have a responsibility to colleagues and collaborators, especially given that research may play a crucial role in capacity building (Garcia and Curioso 2008 ). Although partnerships with local researchers have been touted as highly valuable (Costello and Zumla 2000 ), these ties may also result in unexpected ethical dilemmas for local researchers if confl icts arise between their research activities and their established local obligations and responsibilities (Richman et al 2012 ). A fourth responsibility of researchers is dedication to the research enterprise.…”
Section: Introductionmentioning
confidence: 99%